The comparison of molecular and morphology-based phylogenies of trichaline net-winged beetles (Coleoptera: Lycidae: Metriorrhynchini) with description of a new subgenus - Bocek, Matej; Bocak, Ladislav (PeerJ, 2017)
Separate morphological and molecular phylogenetic analyses are presented and the classification of trichaline net-winged beetles is revised. The clade, earlier given a subfamily, tribe or subtribe rank, is a terminal lineage in Metriorrhynchina and contains Diatrichalus Kleine, 1926, Eniclases Waterhouse, 1879, Flabellotrichalus Pic, 1921, Lobatang Bocak, 1998, Microtrichalus Pic, 1921, Schizotrichalus Kleine, 1926, and Trichalus Waterhouse, 1877. Maibrius subgen. nov. is proposed in Flabellotrichalus with the type-species Flabellotrichalus (Maibrius) horaki sp. nov. Unlike previous studies, Lobatang is included in the trichaline clade. Further, Spinotrichalus Kazantsev, 2010, stat. nov. is down-ranked to the subgenus in Lobatang Bocak, 1998 and a new combination, Lobatang (Spinotrichalus) telnovi (Kazantsev, 2010) comb. nov., is proposed. The morphology does not provide a sufficient support for robust phylogeny due to the intrageneric variability of most phenotypic traits and the limited number of characters supporting deep relationships. Most morphological generic diagnoses must be based on the shape of male genitalia. Other characters, such as the shapes of pronotum and antennae are commonly variable within genera. The fronto-lateral pronotal ridges of Eniclases + Schizotrichalus resemble the ancestral condition in Metriorrhynchini and they re-evolved in the terminal clade and do not indicate the early split of Eniclases + Schizotrichalus from other trichaline genera. The evolution of morphological traits and the conflict in the morphological and molecular phylogenetic signal are discussed in details. We suggest that the general appearance is affected by the evolution of mimetic complexes, the patterns of elytral costae by their strengthening function, and the presence of flabellate antennae by their role in sexual communication. Then, similar phenotypic traits evolve in unrelated lineages. The results demonstrate that phylogenetic classification must be based on all available information because neither morphological traits nor DNA data robustly support all recovered relationships.
Keywords: Phylogeny; Morphology; New taxa; Australian region; New synonym; Oriental region; Molecular phylogeny